The Influence of Tamansiswa Tetep, Mantep, Antep, and Tax Morale Teachings on the Intention to Comply with Prospective Taxpayers from an Islamic Perspective - Wardani, Dewi Kusuma; Wulandari, Dyah Ayu (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
Taxation is a contribution from the people as taxpayers that is paid to the state, in this case, tax is an obligation that is forced with compensation that is not given directly by the government. The benefits of this tax are used to finance the needs of the government to the implementation of the state government which is used to regulate the socio-economic and prosperity of the people. In this case, taxes must be emphasized to be obeyed because they are in the interests of the Indonesian people. In this case, the researcher will examine the intention to comply with prospective taxpayers. Currently, the community, especially prospective taxpayers, has begun to have the intention in their souls to comply with taxation. In addition, data on the increase in tax compliance has also begun to increase among taxpayers. In this case, the study was also reviewed from an Islamic perspective. This study aims to test whether the teachings of Tamansiswa Tetep, Mantep, Antep, and Tax Morale influence the intention to comply with prospective taxpayers. The study uses a quantitative approach. Using primary data. The population in this study were students throughout the Special Region of Yogyakarta. The sample in this study was 150 respondents. The method used in this study was snowball sampling. Data collection was carried out using a questionnaire distributed online using the Google Form application. This study was processed using the SPSS version 23 application. The results of this study indicate that the teachings of tamansiswa tetep, mantep, antep (X1) have a positive effect on the intention to comply with prospective taxpayers, and tax morale (X2) has a positive effect on the intention to comply with prospective taxpayers. This study indicates that efforts to improve the teachings of tamansiswa tetep, mantep, antep, and tax morale can be a major direction to increase the intention to comply with prospective taxpayers. This study is also viewed from an Islamic perspective, namely as in QS. Al Baqarah verse 286 reads "Allah does not burden a person but according to his ability". This is in line with a person's ability to comply with taxes.